Transporter Genes and fosA Associated With Fosfomycin Resistance in Carbapenem-Resistant Klebsiella pneumoniae - Wang, Yu-Ping; Chen, Yen-Hao; Hung, I-Cheng; Chu, Po-Hsun; Chang, Yu-Han; Lin, Yi-Tsung; Yang, Hung-Chih; Wang, Jin-Town (Frontiers in Microbiology, 2022)
Infections caused by carbapenem-resistant Klebsiella pneumoniae (CRKP) are of significant clinical concern worldwide. Fosfomycin is one of the limited treatment options for CRKP. However, resistance to fosfomycin in CRKP has been observed. In this study, we aimed to investigate the fosfomycin resistance mechanism of CRKP. Fosfomycin-resistant Klebsiella pneumoniae isolates were collected from four medical centers in Taiwan from 2010 to 2018. The genes that contributed to fosfomycin resistance were amplified and sequenced. Carbohydrate utilization assays and mutagenesis studies were performed to determine the mechanisms underlying fosfomycin resistance. Forty fosfomycin-resistant CRKP strains were collected and used for further analysis. Fourteen strains exhibited low-level resistance (MIC = 256–512 mg/dl), while 26 strains showed high-level resistance (MIC ≥ 1024 mg/dl). Chromosomal fosAKP I91V was detected in 39/40 fosfomycin-resistant CRKP strains. We observed that amino acid substitution of chromosomal fosAKP I91V increased the MIC of fosfomycin by approximately 8 folds, and this was the only mechanism elucidated for low-level fosfomycin resistance. Among the 26 high-level resistance strains, fosAKP I91V combined with transporter deficiencies (18/26, 69.2%) was the most common resistant mechanism, and one strain showed transporter deficiency only. Plasmid-borne fosA3 accounted for 27.0% (7/26) of high-level resistance. Various G3P and G6P transporter gene mutations, including three novel single amino acid mutations (glpT E299D, glpT D274V, and uhpC A393V) were detected in 19 strains. No murA mutation was found in this study. Our study highlights the need for new therapeutic agents for CRKP infections in Taiwan.